An investigation into the instructional strategies to develop speaking skills for the second year students at Vinh Phuc Teacher Training College = Nghiên cứu chiến lược giảng dạy nhằm nâng cao kỹ năng nói cho sinh viên năm thứ hai Trường Cao đẳng Sư phạm Vĩnh Phúc. M.A Thesis Linguistics: 60 14 01 11 - Đỗ, Thị Cẩm Vân (2017)
The study is entitled “An investigation into the instructional strategies to develop speaking skills for the second year students at Vinh Phuc Teacher Training College”. It was conducted to examine the second year students’ difficulties in their English speaking skills, find out the instructional strategies applied by English language teachers in speaking classes, and show how role-play practice affecting students’ performance in speaking skills. The study was carried out on sixty second-year students and fifteen English teachers at Vinh Phuc Teacher Training College during 8 weeks by questionnaires, semi-structured interviews, test, and personal observations. The findings indicated students’ good awareness and varied attitudes towards the probl ems they have to face, and the difficulties they had in the learning process. In addition, the study showed a range of the instructional strategies the teachers applied to motivate their students’ participation in speaking lessons. And role-playing was the most popularly used at Vinh Phuc Teacher Training College.